2024
DOI: 10.1681/asn.0000000000000326
|View full text |Cite
|
Sign up to set email alerts
|

Combination Treatment with Verinurad and Allopurinol in CKD

Hiddo J.L. Heerspink,
Austin G. Stack,
Robert Terkeltaub
et al.

Abstract: Background: Hyperuricemia is associated with elevated risks of cardiovascular and chronic kidney disease (CKD). Since inhibition of urate transporter 1 has been suggested to be potentially nephroprotective, we performed a phase 2b study to assess albuminuria lowering effects of the urate transporter 1 inhibitor verinurad combined with the xanthine oxidase inhibitor allopurinol in patients with CKD and hyperuricemia. Methods: In this randomized placebo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…However, some glowing embers of enthusiasm re-emerged in early 2021 with the publication of the 60-participant CITRINE trial, on the effects of a verinurad and febuxostat combination on albuminuria in patients with type 2 diabetes; this combination therapy reduced albuminuria by approximately 39%. 8 The uricosuric verinurad, developed by Ardea Biosciences and licensed by AstraZeneca, is a highaffinity inhibitor of the apical urate-anion exchanger URAT1. Like its predecessor lesinurad, verinurad monotherapy can be associated with AKI, potentially analogous to the exerciseassociated AKI seen in patients with renal hypouricemia due to loss-of-function mutations in URAT1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, some glowing embers of enthusiasm re-emerged in early 2021 with the publication of the 60-participant CITRINE trial, on the effects of a verinurad and febuxostat combination on albuminuria in patients with type 2 diabetes; this combination therapy reduced albuminuria by approximately 39%. 8 The uricosuric verinurad, developed by Ardea Biosciences and licensed by AstraZeneca, is a highaffinity inhibitor of the apical urate-anion exchanger URAT1. Like its predecessor lesinurad, verinurad monotherapy can be associated with AKI, potentially analogous to the exerciseassociated AKI seen in patients with renal hypouricemia due to loss-of-function mutations in URAT1.…”
mentioning
confidence: 99%
“…To follow up on the promising results of CITRINE, AstraZeneca and collaborators designed the Study of ver-inurAd and alloPurinol in Patients with CKD and hyperuricemia trial, the results of which are published in this issue of JASN. 8 Owing to the results of the CARES trial, which suggested an excess of cardiovascular mortality for febuxostat compared with allopurinol, 7 the investigators substituted allopurinol as the xanthine oxidase inhibitor for the Study of verinurAd and alloPurinol in Patients with CKD and hyperuricemia trial. The trial enrolled a total of 861 adults with CKD and eGFR $25 ml/min per 1.73 m 2 , urinary albumin-to-creatinine ratio between 30 and 5000 mg/g, and serum urate $6.0 mg/dl.…”
mentioning
confidence: 99%